2016
DOI: 10.1088/0953-8984/28/16/166003
|View full text |Cite
|
Sign up to set email alerts
|

Europium and manganese magnetic ordering in EuMn2Ge2

Abstract: The antiferromagnetic structures of both the manganese and europium sublattices in EuMn2Ge2 have been determined using thermal neutron diffraction. T(N)(Mn)  =  714(5) K with the 3.35(5) μ(B) (at 285 K) Mn moments ordering according to the I4'/m'm'm space group. The Eu order is incommensurate with the 6.1(2) μ(B) (at 3.6 K) Eu moments oriented parallel to the c-axis with a propagation vector of k  =  [0.153(2) 0 0]. Both neutron diffraction and (151)Eu Mössbauer spectroscopy reveal evidence of magnetic short-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[14] The wide range of behavior exhibited by the REMn 2 X 2 materials is related to the rich diversity of collinear and non-collinear magnetic states that can be realized in this atomic arrangement. [15][16][17][18][19][20][21][22][23][24][25][26] Magnetic ordering temperatures between 300 K and 714 K have been observed for all compounds of this type, [1,27] and many of them undergo several magnetic transitions upon cooling before they reach their magnetic ground state. Previous studies on various solid solutions based on REMn 2 X 2 indicated that the Mn-Mn distances play a major role in the formation of different magnetic structures.…”
Section: Introductionmentioning
confidence: 99%
“…[14] The wide range of behavior exhibited by the REMn 2 X 2 materials is related to the rich diversity of collinear and non-collinear magnetic states that can be realized in this atomic arrangement. [15][16][17][18][19][20][21][22][23][24][25][26] Magnetic ordering temperatures between 300 K and 714 K have been observed for all compounds of this type, [1,27] and many of them undergo several magnetic transitions upon cooling before they reach their magnetic ground state. Previous studies on various solid solutions based on REMn 2 X 2 indicated that the Mn-Mn distances play a major role in the formation of different magnetic structures.…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of behavior exhibited by the RE Mn 2 X 2 materials is related to the rich diversity of collinear and non-collinear magnetic states that can be realized in this atomic arrangement 15 26 . Magnetic ordering temperatures between 300 and 714 K have been observed for all compounds of this type 1 , 27 , and many of them undergo several magnetic transitions upon cooling before they reach their magnetic ground state. Previous studies on various solid solutions based on RE Mn 2 X 2 indicated that the Mn–Mn distances play a major role in the formation of different magnetic structures.…”
Section: Introductionmentioning
confidence: 99%